PEMETAAN LAHAN KRITIS UNTUK KAJIAN PENATAAN RUANG DI KABUPATEN TABANAN - Putra, Akbar Cahyadhi Pratama; Widhaningtyas, Tantri Utami; Fariz, Trida Ridho (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
Tabanan Regency is one of the areas with a fairly rapid level of development through an increasing tourism and trade sector. Topographically, Tabanan Regency is also an area with a diverse topography. These two conditions make this area a potential critical land phenomenon. This study aims to map critical land in Tabanan Regency using spatial analysis based on GIS (Geographical Information System) and remote sensing and analyze the linkages of critical land with existing land use and analysis of spatial planning studies of the Spatial Planning of Tabanan Regency. The analysis used uses the overlay method of several thematic map parameters. To determine the value of each parameter using the scoring method. The results of the analysis show that in Tabanan Regency 60408.66 Ha or 71% is non-critical land, while 104.46 Ha or <1% is very critical land. The distribution of land use that has very critical land conditions is mostly dominated by existing land use settlements. In terms of spatial planning, the Spatial Planning zones of residential areas also fall into the category of very critical land conditions. It is necessary to regulate residential area zones to pay attention to the function of water catchment.